(untitled) (International Educators Conference, 2025)
This article explores the Audio-Lingual Method, a language teaching approach rooted in behaviorist psychology that gained popularity in the mid-20th century. It emphasizes habit formation through drills, repetition, and memorized dialogues, prioritizing speaking and listening over reading and writing. The method discourages the use of the native language and avoids explicit grammar explanations, aiming instead to teach grammar inductively. While the method strengthens oral skills and provides a structured learning environment, it has been criticized for being mechanical, lacking communicative focus, and offering limited opportunities for creativity. The annotation highlights that although the method can be effective for beginner-level learners and pronunciation practice, it is less suited for developing comprehensive language competence in real-world contexts.